The Customer Catalyst : How to Drive Business Growth in the Customer Economy. - Bausor, Daniel (John Wiley & Sons, Incorporated, 2019)
How organisations can drive growth in the Customer Economy. The Digital Revolution has changed the business landscape in remarkable ways and will continue to do so. Organisations across industries and around the world are being disrupted and digitised at increasing pace - putting far more power in the hands of both customers and end-consumers. The traditional inside-out, functionally-siloed business model, typical of the product and sales-led growth era is over. The Customer Catalyst shows how organisations can put customers truly at the heart of their business and catalyse genuine, sustainable growth.' Future business models are no longer about functions - they are beginning to revolve around customers. Customer-led companies will, over time, unpack their static functional activities and transform their structure. Customer advocates already wield massive influence in a customer's buying process, and this is only set to increase. This is already changing the role and nature of business functions and Sales is no longer seen as the only source of growth. The Customer Economy is placing greater demands on businesses and offers greater rewards to the businesses that meet and exceed customer expectations. This invaluable book will enable readers to: -Lead their organisations to more profitable and sustainable growth -Transform their organisations to become truly customer-centric with the C-change growth engine -Explore in-depth stories from leaders of companies such as Zoom, Signify, Starling Bank, Ritz Carlton, Microsoft and Finastra with frank advice and practical steps'to achieve success -Help their companies adapt to, and profit from, the new realities of the Customer Economy -Gain important insights from business leaders on best practice in key customer-centric growth areas The Customer Catalyst shows businesses how to survive the transition to the Customer Economy, transform to align around today's dynamic customer needs, and ultimately, drive sustainable business growth.